A triangle has vertices at R(1, 1), S(-2,-4), and T-3, -3). The triangle is transformed according to the rule Ro. 270". Whatare the coordinates of S?


(-4,2)
(-2, 4)
(2,4)
(4,-2)

Answers

Answer 1
Answer:

The coordinate of S if the triangle is transformed according to the rule Ro. 270 is (-4, 2)

Transformation of coordinates

Transformation is the process of changing the position of an object in a xy-plane.

Given the coordinate of the triangles as R(1, 1), S(-2,-4), and (T-3, -3). If the triangle is transformed according to the rule Ro. 270", the resulting coordinate points are (x,y)→(y,−x)

The coordinate of S using the rule is (-4, 2)

Learn more on transformation here: brainly.com/question/17311824

Answer 2
Answer:

The coordinate of S if the triangle is transformed according to the rule Ro. 270 is (-4, 2)

What is transformation?

A transformation is a dramatic change in form or appearance. An important event like getting your driver's license, going to college, or getting married can cause a transformation in your life. A transformation is an extreme, radical change.

here, we have,

Transformation of coordinates

Transformation is the process of changing the position of an object in a xy-plane.

Given,

the coordinate of the triangles as R(1, 1), S(-2,-4), and (T-3, -3). If the triangle is transformed according to the rule Ro. 270", the resulting coordinate points are (x,y)→(y,−x)

The coordinate of S using the rule is (-4, 2)

Learn more on transformation here:

brainly.com/question/17311824

#SPJ5


Related Questions

Three friends share 2 sandwiches
Mary says the pen for her horse is an acute an right triangle. Is that possible. explain
Use row operations to solve the systemx + y – z = -24x – y + z = 7X – 3y + 2z =-5
Mr. Carter is planning a special event for 98 guests. A catering company tells him that the cost of food for each guest will be $16. The cost for drinks for each guest will be another $5. Based on that, Mr. Carter works out that the total catering bill will be $20,580. Does that sound about right?
How can i divide 3 divided by 681

Multiply. Simplify your answer and write it as a proper fraction or as a whole or mixed number.35 × 1/2 = 

Answers

do 35/1 and then make 1 1/2 into an improper fraction (which is 3/2) and you do 35/1 * 3/2 you should get 105/2 and then make it into an mixed fraction.
35*1 (1)/(2) =35*(3)/(2)=(3*35)/(2)=(105)/(2)=52(1)/(2)   or   52.5

Enter the value of p so the expression 5/6-1/3n is equivalent to p(5-2n)? Please show your steps, I am really lost

Answers

P needs to be something that is multiplied through 5-2n to equal 5/6-1/3n.  Since you see that there is a 5 of somesort in both equations an easy place to start is simply making p=1/6.  Once you do that then 5*1/6=5/6 so the first part is okay. Then 2n*1/6=2n/6 which is able to be reduced to n/3.
Based on this it is clear that p should equal 1/6.

I don't understand how to do this can someone pls help me

Answers

Take 2^30(gigabyte) and plug into a calculator
then take 2^20(megabyte) and plug into calculator
divide
1024

12. Shreyas orders a pizza for himself and eats 5/8 of the entire pizza. The next day he eats 1/3 of the remaining pizza as a snack after school. b) If the entire pizza contained 2500 calories, how many calories did Shreyas consume on the first day?

Answers

Answer:

1562.5 calories

Step-by-step explanation:

Shreyas ate (5)/(8) of the entire pizza on the first day.

Entire pizza contained calories = 2,500

Therefore, Shreyas consumed calories on the first day  = (5)/(8) of 2500

= (5)/(8) × 2500

= 0.625 × 2500

= 1,562.5 calories

Shreyas consumed 1,562.5 calories on the first day.

Answer:

1562.5

Step-by-step explanation: 2500 divided by 8 times 5

8×4= (?×7)-(?×3)

Can u sove the equation^

Answers

8*4 = 32

Now, we need to solve this:-

32 = (?*7) - (?*3)
32=8*7 - 8*3
32= 56 - 24
32 = 32

So our equation is:-

8*4 = (8*7) - (8*3)



so solve for ?
we use commutative which is a(bc)=(ab)c or also =abc
remember that (? times 7)=1(? times7)=1 times ? times 7=? times 7=7?
and
-(? times 3)=-1(? times 3)=-1 times ? times 3=  -? times 3=-?3=-3?
so we have
8 times 4=7?-3?
7? means 7 times ? so therefor 7?-3?=7 times of ?  -3  times of ?=7-3=4 times of ? so 4?
8 times 4=4?
multiply divide both sides by 4
8=?

Please help me out!!❤️

Answers

Natalie would have been making a mistake from the beginning because any non-zero expression raised to the power of zero is one.

So she would have been making a mistake from step one